2020
DOI: 10.1002/anie.201911660
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinium Salts as Redox‐Active Functional Group Transfer Reagents

Abstract: In this Review, we highlight recent advances in the understanding and design of N‐functionalized pyridinium scaffolds as redox‐active, single‐electron, functional group transfer reagents. We provide a selection of representative methods that demonstrate reactivity and fundamental advances in this emerging field. The reactivity of these reagents can be divided into two divergent pathways: homolytic fragmentation to liberate the N‐bound substituent as the corresponding radical or an alternative heterolytic fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
112
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(117 citation statements)
references
References 176 publications
(115 reference statements)
2
112
0
Order By: Relevance
“…35 A milder version of this photochemical process was recently disclosed by DiRocco, Krska and co-workers by using 4 [Ir(dF-CF3-ppy)2(dtbpy)]PF6 as the photocatalyst an benzoyl peroxide (PBO) as the terminal oxidant. 39 Based on the dual reactivity of N-alkoxypyridinium ions (NAPs), 40,41,[42][43][44][45] as alkoxy radical precursors that are good hydrogen abstractors 46,47,48 and as electrophilic partners in Minisci reactions, as previously reported by Hong and co-workers [49][50][51][52][53][54][55]56 we hypothesized that NAPs should be good partner with silanes or methanol to accomplish photocatalytic C-H silylation and hydroxymethylation, respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…35 A milder version of this photochemical process was recently disclosed by DiRocco, Krska and co-workers by using 4 [Ir(dF-CF3-ppy)2(dtbpy)]PF6 as the photocatalyst an benzoyl peroxide (PBO) as the terminal oxidant. 39 Based on the dual reactivity of N-alkoxypyridinium ions (NAPs), 40,41,[42][43][44][45] as alkoxy radical precursors that are good hydrogen abstractors 46,47,48 and as electrophilic partners in Minisci reactions, as previously reported by Hong and co-workers [49][50][51][52][53][54][55]56 we hypothesized that NAPs should be good partner with silanes or methanol to accomplish photocatalytic C-H silylation and hydroxymethylation, respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 95%
“…It should be noted that Lei et al 57 reported a practically simple hydroxymethylation of a large variety of quinolines and isoquinolines in the presence of substoichiometric amounts of Selectfluor ® . 41 Unfortunately, pyridines were found to be unreactive under their optimized conditions, thus, calling for an alternative approach which would be complementary to Lei's method. With this in mind, we reacted methanol (4) with different N-methoxypyridinium ions (1) under the optimized conditions described above (Figure 2).…”
mentioning
confidence: 99%
“…The breadth of available transformations make pyridinium salts valuable templates for accessing functionalized 6-membered aza-heterocyclic scaffolds, which are prevalent in agrochemicals, alkaloid natural products, and are the most commonly encountered heterocyclic motif in FDA approved small molecule drugs 19 . In addition to manipulations of the heterocyclic ring, pyridinium salts can undergo ring openings to produce Zincke aldehydes, which have shown utility as synthetic building blocks 20 , and 2,4,6-triphenylpyridinium salts have emerged as a new and powerful class of radical precursors for deaminative metal-catalyzed cross couplings ( Figure 1b) 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of N-substituted pyridinium salts for reductive fragmentation, as postulated in the mechanism, was studied in detail elsewhere and was outlined recently in a review. [30] Next, we conducted a series of optimization and control experiments to prove the necessity of individual reaction components. As already pointed out, in the dark no product formation was observed.…”
mentioning
confidence: 99%